2008
DOI: 10.1002/anie.200704619
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Direct Arylation of (Hetero)Arenes with Aryl Boronic Acids

Abstract: No compass required: A method is described for forming biaryl CC bonds by a PdII‐catalyzed cross‐coupling of aryl CH bonds with aryl boronic acids under mild conditions without the presence of directing groups. Different substituents on both (hetero)arenes and aryl boronic acids are compatible with the reaction conditions, and the homocoupling of boronic acids is highly inhibited. Dioxygen was applied as the final oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
113
0
5

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(120 citation statements)
references
References 58 publications
2
113
0
5
Order By: Relevance
“…The solvent was removed to give corresponding indole compound 6 as white solid. The structures of 6a [22], 6b [23], 6c [21], 6d [24], 6e [25], 6f [22], 6g [25], 6h [22], 6i [23], 6j [19] and 6l [26] were referred to the reported data.…”
Section: General Procedures For Intramolecular Hydroamination Of Alkynementioning
confidence: 98%
“…The solvent was removed to give corresponding indole compound 6 as white solid. The structures of 6a [22], 6b [23], 6c [21], 6d [24], 6e [25], 6f [22], 6g [25], 6h [22], 6i [23], 6j [19] and 6l [26] were referred to the reported data.…”
Section: General Procedures For Intramolecular Hydroamination Of Alkynementioning
confidence: 98%
“…Obviously, the direct arylation of arenes with arylboron reagents, in which prehalogenation of the arene coupling partners is not required, may provide a straightforward and environmentally benign method for biaryl synthesis [7][8][9][10][11][12][13][14]. As an example for the direct reaction, we have reported the multiple phenylation of benzonitrile using sodium tetraphenylborate under rhodium catalysis (Scheme 1) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al described a Pd IIcatalyzed cross-coupling of electron-rich heteroarenes (i.e., pyrrole, furan, and thiophene derivatives) with arylboronic acids under mild conditions. [4] Studer et al reported the first direct C À H arylation of indoles with arylboronic acids and the 2,2,6,6-tetramethylpiperidine N-oxyl radical (TEMPO) as an external mild oxidant at room temperature. [5] Although the aryl-azole structural motifs are ubiquitous in biologically important natural products, synthetic pharmaceuticals, and materials, [6] it is unknown that the direct C À H arylation of azoles with arylboronic acid hitherto.…”
mentioning
confidence: 99%
“…Whereas p-electron excessive five-membered heterocycles (i.e., thiophenes, furans, and pyrroles) smoothly coupled with arylboronic acids through an electrophilic mechanism, the azoles investigated herein gave only trace amount to low yields of the desired products. [4,5] Although both types of heteroarenes are electron-rich, the C2 sites of azoles are relatively electrondeficient. We believe that the distinctly differential p-electronic characteristics may induce the clear distinctness of reactivity.…”
mentioning
confidence: 99%